FAKTOR PENGHAMBAT ALOKASI LUAS LAHAN KEBUN PLASMA SEBAGAI SYARAT PEROLEHAN HAK GUNA USAHA PERKEBUNAN KELAPA SAWIT - MUTIARA PANJAITAN (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing;1.  Prof. Dr. Muhd. Yamin, SH, MS, CN2.  Prof. Dr. Saidin, SH, MHum3.  Notaris Dr. Suprayitno, SH, MKn The research used descriptive juridical normative method with statue approach. Secondary data were obtained from primary, secondary and tertiary legal materials. They were gathered by conducting library research and field research method as well as interview and analyzed qualitatively. The result of the research shows that there is the difference or overlapping in the regulation on allocating plasma plantation to the people, based on Permentan RI No. 98/2013 and Permen No. 7/2017. The inhibiting factors in allocating plasma plantation by oil palm plantations were that the regulation was not consistent and the mechanism of implementing it was uncertain. The effort to solve them was by completing the regulation of plantation licensing among the government agencies, especially the Ministry of Agriculture and the Ministry of Agrarian Affairs and Layout.Key Words : Plasma Plantation, Allocation of Land Area, Leasehold, Oil Palm Plantation